Exploring the Link Between Cardiovascular Fitness, Metabolic Syndrome, and Heart Rate Variability in Anesthesiology Residents at Airlangga University - Anwar, Dhikrulloh; Atsira, Olga Putri; Surya Airlangga, Prananda; Argarini, Raden (Journal of Neonatal Surgery, 2025)
Background: Cardiorespiratory fitness (CRF) is a key indicator of aerobic capacity and plays a crucial role in cardiovascular and autonomic nervous system health. Metabolic syndrome (MetS), characterized by abdominal obesity, hyperglycemia, dyslipidemia, and hypertension, increases cardiovascular disease risk and impairs autonomic function. Heart rate variability (HRV) is a noninvasive measure of autonomic balance and cardiovascular health. Objective: This review explores the interrelationship between CRF, MetS, and HRV, emphasizing its implications for anesthesiology and intensive care residents, who experience high stress and workload. Methods: A literature review was conducted to assess how CRF influences HRV and mitigates MetS-related autonomic dysfunction. Findings: Higher CRF is associated with increased HRV, indicating better autonomic regulation, while MetS is linked to reduced HRV and impaired cardiovascular function. Maintaining optimal CRF appears to counteract MetS-related autonomic imbalances, reducing cardiovascular risks in high-stress professions. Conclusion: Enhancing CRF through structured physical activity may serve as a preventive strategy against MetS-related autonomic dysfunction and cardiovascular disease, particularly for medical professionals exposed to chronic stress. Workplace interventions promoting physical fitness could play a crucial role in safeguarding the well-being of anesthesiology residents.